π0-η-η′ mixing from V → Pγ and P → Vγ decays - Rafel Escribano; Emilio Royo (Physics Letters B, 2020)
An enhanced phenomenological model that includes isospin-symmetry breaking is presented in this letter. The model is then used in a number of statistical fits to the most recent experimental data for the radiative transitions VPγ (V=ρ, K⁎, ω, ϕ and P=π, K, η, η′) and estimations for the mixing angles amongst the three pseudoscalar states with vanishing third-component of isospin are obtained. The quality of the performed fits is good, e.g. χmin2/d.o.f=1.9. The current experimental uncertainties allow for isospin-symmetry violations with a confidence level of approximately 2.5σ.